1998
DOI: 10.1161/01.cir.97.18.1837
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Coronary Heart Disease Using Risk Factor Categories

Abstract: Background-The objective of this study was to examine the association of Joint National Committee (JNC-V) blood pressure and National Cholesterol Education Program (NCEP) cholesterol categories with coronary heart disease (CHD) risk, to incorporate them into coronary prediction algorithms, and to compare the discrimination properties of this approach with other noncategorical prediction functions. Methods and Results-This work was designed as a prospective, single-center study in the setting of a community-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

135
5,765
17
275

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 8,186 publications
(6,290 citation statements)
references
References 66 publications
135
5,765
17
275
Order By: Relevance
“…Further, only the MPI remained an independent predictor of ICVD in participants with hypertension (MPI: SHR, 1.12 [95% CI 1.01–1.23] per 0.1 increase, P =0.027) (Figure 8D). In addition, reclassification analysis demonstrated that adding IVRT/ET or MPI to the clinical predictors from the Framingham Risk Score32 and the SCORE risk chart34 (age, sex, cholesterol, smoking status, and SBP) yielded better predicting models with significant increase in the categorical net reclassification improvement of 0.0227 (95% CI 0.0017–0.0437, P =0.034) for IVRT/ET and 0.402 (95% CI 0.0150–0.0653, P =0.002) for the MPI, respectively. Additionally, reclassification analysis demonstrated that adding IVRT/ET or MPI to a model including the clinical predictors from the newer ESH/ESC risk chart1 (age, sex, smoking status, cholesterol, diabetes, SBP, DBP, LVH, chronic kidney disease [defined as estimated glomerular filtration rate ≤60 mL/min per 1.73 m 2 ], IHD, and ischemic stroke) yielded better predicting models with significant increase in the categorical net reclassification improvement of 0.0341 (95% CI 0.0079–0.0603, P =0.011) for IVRT/ET and 0.344 (95% CI 0.0039–0.0648, P =0.027) for the MPI, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Further, only the MPI remained an independent predictor of ICVD in participants with hypertension (MPI: SHR, 1.12 [95% CI 1.01–1.23] per 0.1 increase, P =0.027) (Figure 8D). In addition, reclassification analysis demonstrated that adding IVRT/ET or MPI to the clinical predictors from the Framingham Risk Score32 and the SCORE risk chart34 (age, sex, cholesterol, smoking status, and SBP) yielded better predicting models with significant increase in the categorical net reclassification improvement of 0.0227 (95% CI 0.0017–0.0437, P =0.034) for IVRT/ET and 0.402 (95% CI 0.0150–0.0653, P =0.002) for the MPI, respectively. Additionally, reclassification analysis demonstrated that adding IVRT/ET or MPI to a model including the clinical predictors from the newer ESH/ESC risk chart1 (age, sex, smoking status, cholesterol, diabetes, SBP, DBP, LVH, chronic kidney disease [defined as estimated glomerular filtration rate ≤60 mL/min per 1.73 m 2 ], IHD, and ischemic stroke) yielded better predicting models with significant increase in the categorical net reclassification improvement of 0.0341 (95% CI 0.0079–0.0603, P =0.011) for IVRT/ET and 0.344 (95% CI 0.0039–0.0648, P =0.027) for the MPI, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…2 (center) compares the lifespan‐predictive ability of the well‐known Framingham Risk Score (Wilson et al ., 1998; Lloyd‐Jones et al ., 2004) and Pooled Cohort Score (Goff et al ., 2014) with our ‘focal exam’ estimates. These clinical scores were designed specifically to assess cardiovascular risk in a 5‐ to 10‐year timeframe, using some of the parameters we examined as well as smoking status, blood cholesterol, and age.…”
Section: Resultsmentioning
confidence: 99%
“…For asymptomatic patients without a history of atherosclerotic cardiovascular disease (ASCVD), risk stratification tools have been developed and validated to provide the foundation for targeted preventive efforts based on the individual's predicted risk with the concept of targeting the intensity of drug treatment interventions to the severity of the patient's cardiovascular risk 22, 23, 24, 25. On the other hand, patients with ASCVD have been referred to as high‐risk patients for whom prompt initiation of guideline‐recommended therapies should be considered to reduce the risk.…”
Section: Discussionmentioning
confidence: 99%